On the meaning of community-level tree-growth signal in a tropical forest restoration - Olmedo, Gabriela Morais; Oliveira, Juliano Morales de; Teixeira, Maycon da Silva; Mores, Guilherme José [UNESP]; Engel, Vera Lex [UNESP]; Tomazello-Filho, Mario (Elsevier, 2025)
Ecological restoration is a global need, particularly in the tropics. Dendrochronological research could boost basic and applied knowledge for tropical restoration projects. Here, we explored whether trees in restoration programs of the Atlantic Rainforest form growth rings prone to crossdating and analysis of climatic signals. We analyzed 43 trees distributed across the 18 most common species in two restoration stands. Trees (35) from all the species evidenced crossdatable growth rings, allowing us to construct a robust multi-species ring-width chronology. This unprecedented community-level signal in the tropics was determined by a one-year lagged tree-growth response to water availability and temperature. The dynamics of non-structural carbohydrates (NSC) are likely involved in this delayed climatic effect. Relatively homogeneous light conditions among trees in the stands would be critical for detecting the growth signal. Whether such a community-level signal would be found elsewhere and the role of NSC in mediating tree growth responses to climate deserve further investigation. Tree-ring analysis allowed us to assess the climatic sensitivity of a forest community undergoing restoration and could further address several other relevant issues towards restoring tropical ecosystems. On the other hand, restoration projects offer a unique experimental setting to advance tropical dendrochronology.
Keywords: Brazilian atlantic rain forest; Climate signal; Monitoring; Multi-species dendrochronology; Non-structural carbohydrates; Tree-rings